Thoracic anesthesia - Kaplan, Joel A; Slinger, Peter D (Churchill Livingstone, 2003)
Univ. of Louisville, KY. Text presents methods, materials, and fundamentals of thoracic anesthesia. Covers thoracic anesthesia and surgery, assessment of the patient, cardiopulmonary physiology, and postoperative intensive care. Written by a Brandon/Hill author. For anesthesiologists and surgeons. Previous edition: c1991.
Keywords: pooperační ošetřování; Thoracic Surgical Procedures; Anesthesia; anestezie; Pain, Postoperative; Postanesthesia Nursing; anesteziologie a intenzivní lékařství; miniinvazivní chirurgické výkony; Postoperative Care; Thoracic Surgery; chirurgie; Minimally Invasive Surgical Procedures; pooperační bolest; pooperační péče; hrudní chirurgické výkony; hrudní chirurgie